Prothrombin Time and Hemorrhagic Death in Dicumarolized Rats Receiving Pituitary and Adrenal Hormones - van Cauwenberge, H; Jaques, L. B (Thrombosis and Haemostasis, 1959)
1. Rats receiving dicumarol were given injections of desoxycorticosterone, cortisone, hydrocortisone, ACTH, somatotropin, sodium salicylate, adrenaline, reserpine, histamine, 10% sodium chloride intraperitoneally. A high incidence of hemorrhagic death was observed with desoxycorticosterone, ACTH, STH, sodium salicylate, 10% sodium chloride, histamine, adrenaline, reserpine. Little hemorrhage was observed with cortisone and hydrocortisone.2. The mortality resulting from 10% sodium chloride stress in dicumarolized rats was not depressed by dial, or phenergan, or pretreatment with cortisone. The mortality was prevented by treatment with vitamin Ki before giving the stress agent.3. The mean prothrombin time with dicumarol in rats appeared to be increased by the administration of ACTH, sodium salicylate, 10% sodium chloride, desoxycorticosterone, adrenaline and histamine. No modification was observed by cortisone, dial, reserpine. With hydrocortisone — there was an increase the day after giving the steroid, but the prothrombin time was nearly normal 2 days later.4. Steroids were tested for their ability to protect adrenalectomized rats from hemorrhage with dicumarol. Desoxycorticosterone had no action in this regard. Cortisone and hydrocortisone were effective with cortisone being more active.